2022
DOI: 10.1155/2022/3208037
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis and Anticoagulation Therapy in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease in which pathogenic autoantibodies and immune complexes are formed and mediate multiple organ and tissue damage. Thrombosis is one of the most common causes of death in patients with SLE. Anticoagulant therapy blocks the vicious cycle between inflammation and thrombosis, which may greatly improve the long-term prognosis of patients with SLE. However, the etiology and pathogenesis of this disease are very complicated and have not yet been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
2
4
0
1
Order By: Relevance
“…Anticoagulant therapies, such as Heparin and Warfarin, can block the vicious cycle between inflammation and thrombosis, which may greatly improve the long-term prognosis of patients with SLE [ 179 ]. Heparin is often used as an initial treatment.…”
Section: Management Of Npslementioning
confidence: 99%
See 1 more Smart Citation
“…Anticoagulant therapies, such as Heparin and Warfarin, can block the vicious cycle between inflammation and thrombosis, which may greatly improve the long-term prognosis of patients with SLE [ 179 ]. Heparin is often used as an initial treatment.…”
Section: Management Of Npslementioning
confidence: 99%
“…There is less evidence available on the use of Warfarin in patients with SLE. However, a prospective multicenter research trial showed that Warfarin (1–5 mg/day) started at the same time as a steroid therapy for at least 3 months can prevent the occurrence of osteonecrosis associated with SLE [ 179 ].…”
Section: Management Of Npslementioning
confidence: 99%
“…bei Patienten mit überlappendem SLE und 3-fach positiven aPL [105]. Eine primäre Thromboseprophylaxe mit Antikoagulanzien wird bei SLE-Patienten nicht empfohlen [106, 107], während eine langfristige Sekundärprophylaxe in Abhängigkeit vom Nutzen-Risiko-Verhältnis erwogen werden sollte.…”
Section: Antikoagulation Bei Patienten Mit Autoimmunerkrankungenunclassified
“…is a systemic autoimmune disease with vascular lesions. Its clinical manifestations vary from mild cutaneous and mucosal diseases to multiple organ involvement [ 92 ].…”
Section: Prospectmentioning
confidence: 99%